Luminescence of Bi3+ Ions in GGG epitaxial films - Luchechko, A.; Syvorotka, I. I.; Zakharko, Ya.; Syvorotka, I. M. (Видавництво Львівської політехніки, 2012)
Absorption, emission spectra under UV and Xray excitations, as well as luminescence decay kinetics of GGG:Bi single crystalline films were studied. The emission spectra observed in the spectral region 350-700 nm at room temperature consist two elementary bands peaked at 446 and 521 nm. The influence of growth conditions on the optical-luminescent properties of GGG: Bi3+ garnet have been revealed. The ratio of the bands intensities in luminescence spectra under different types of excitation and their temperature dependencies were determined.
Keywords: Gd3Ga5O12: Bi3+ epitaxial films; photo- and X-ray luminescence; decay time